ANALISIS FAKTOR YANG MEMENGARUHI INDEKS PEMBANGUNAN MANUSIA PADA 7 DAERAH TERTINGGAL DI PULAU SUMATERA TAHUN 2016-2020 - Ainia, Churrotul; Suharso, Pudjo; Hartanto, Wiwin (JAMI: Jurnal Ahli Muda Indonesia, 2023)
One of the criteria in determining underdeveloped areas is the quality of human resources which there is an increase in quality of human resources it will increase the community’s welfare. But in fact, Sumatera Island contributed 7 out of 62 underdeveloped areas in Indonesia since 2020. It can be caused by the criteria of determining underdeveloped areas, which is looking at the quality of human resources. The indicator that is often used in measuring human resource development is the Human Development Index (HDI) which divided into three factors, namely poverty, healthiness, and education. The aims of this study was to analyze the factors that influence the human development index in 7 underdeveloped areas on the Sumatera Island. This study is quantitative research methods using secondary data in the form time series data from 2016 to 2020 and cross section data of 7 districts analyzed by panel data regression analysis with Eviews 9 program. The results of this study indicate that the poverty have a negative and insignificant on HDI. Moreover, healthiness and education has significantly positive effect on HDI. All of variables in this study explain 93,24% of towards HDI in underdeveloped areas.